3(x-9)=50

Simple and best practice solution for 3(x-9)=50 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-9)=50 equation:


Simplifying
3(x + -9) = 50

Reorder the terms:
3(-9 + x) = 50
(-9 * 3 + x * 3) = 50
(-27 + 3x) = 50

Solving
-27 + 3x = 50

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '27' to each side of the equation.
-27 + 27 + 3x = 50 + 27

Combine like terms: -27 + 27 = 0
0 + 3x = 50 + 27
3x = 50 + 27

Combine like terms: 50 + 27 = 77
3x = 77

Divide each side by '3'.
x = 25.66666667

Simplifying
x = 25.66666667

See similar equations:

| 5y+3=8y+13 | | 4x-3(3x-7)=56 | | 5v-15=60 | | 7x-4(2x-3)=3 | | X^2+2X+-2=0 | | 0.5x+2=0.3x+6 | | 4x-3(7x-6)=-101 | | 2x(-1)=x-3 | | 3x-2y+5z=250 | | X+35=8x | | 8-9+7w=7w | | 25=z-4 | | 2x-7=-17+x | | A+(8+a)+a=125 | | -3x+6(-3x+5)=-75 | | 5x+3x-8=9(x-2) | | 9/2-2=d | | 3x+5(-3x+12)=-12 | | 7a^2+34a+40=0 | | 11-y=203 | | t+1-4t+8=8 | | b-1+3b=28 | | 3p+5=p+19 | | 51=-5x+3(6x-9) | | 4(3c-1)-1=10c+9 | | -4x+7(-x+8)=1 | | 8/2+1=c | | 6y+14+4=32 | | -3x-6(x+8)=60 | | -3pq+spr-7p-6=-6q-5 | | 2a+(a+87)=180 | | .3333x=9 |

Equations solver categories